Nitrogen source and rate effects on irrigated potato in tropical sandy soils - Souza, Emerson F. C. [UNESP]; Soratto, Rogério P. [UNESP]; Fernandes, Adalton M. [UNESP]; Rosen, Carl J. (Wiley, 2019)
A suitable N source and an optimal application rate can improve the N-use efficiency of potato (Solanum tuberosum L.) while minimizing N losses, especially when potato is grown in sandy soils. Three experiments were conducted at irrigated sandy soil sites in São Paulo State, Brazil, to evaluate the effects of ammonium sulfate (AMS), ammonium sulfate nitrate with the nitrification inhibitor 3,4-dimethylpyrazole phosphate (ASN+DMPP), and urea applied at three N rates (80, 120, and 160 kg ha –1 ), as well as a zero-N control on potato (cv. Agata). Leaf N and S concentrations, tuber yield, and agronomic efficiency (AE) were measured. The 80 kg N ha –1 rate was applied in the furrow at planting, and the other rates were split-applied, with 40 kg N ha –1 in the furrow at planting and the remainder applied at hilling. Regardless of the N source, the N fertilizer rates increased the potato leaf N concentration and tuber bulking of the potato crop, which in turn increased the tuber yield up to rates between 136 kg N ha –1 and at least 160 kg N ha –1 . Among the N sources, ASN+DMPP fertilizer resulted in a higher potato tuber set and yield than urea and led to the highest AE compared to AMS and urea. Overall, these results suggest the potential for ASN+DMPP to improve the synchronization between soil N availability and potato N demand and provide a more appropriate balance of N forms in the soil when potato is cultivated in sandy soils in a tropical climate.